Aplikasi Tablet Interaktif In-Room Guest Services Bebasis Android Pada Hotel Grand Duta Palu - Putri Belina Tandra; Justinus Andjarwirawan; Yulia Yulia (Jurnal Infra, 2017)
Android In-Room Guest Interactive Tablet Applications at Grand Duta Hotel in Palu. Currently, Grand Duta Hotel still manages the ordering process manually. The ordering process that still uses the phone sometimes happens a miss commucation error. This resulted in the reservation being delayed or ordering not as desired. Features found in this application hotel guests can place orders in each section. For example in the Room Service for ordering food or drinks. This process is directly connected to the Room Service without having to go through the Front Desk again.The end result of this application development is able to make the ordering process online, can receive direct notification about the order can be processed or not. And facilitate employees in checking orders from guests.